Classification by Greater Use Capacity of the Lands of the Rural Community San Damián, Cascapara, Yungay, Ancash (Aporte Santiaguino, 2023)
- 1 - Taking into account the great diversity of the physical environment, where family farming is developed, the study of land classification by greater Use Capacity of the agricultural lands of the San Damián Peasant Community was carried out in order to know the use (what crops can be conducted in the areas studied), the problems or limitations that these lands may have, and the most appropriate management practices that should be applied. The results showed that due to the ruggedness of the terrain, of the 300 hectares covered by the study, the largest areas correspond to land suitable for pasture (P) with 114 hectares, (38,28%), then there are lands suitable for permanent crops (C) 94,60 ha (31,53%), then there are the protection areas (X), with 55,66 ha (18,55%); then there are the lands suitable for forestry (F) with 19,21 hectares (6,40%) and finally there are the best lands, suitable for diversified agriculture (A) with 15,69 hectares, which represent only 5,23% of the total areas studied. Of course, the peasant producer uses the land according to his own criteria, but always maintaining biodiversity, rational management and a limited use of agrochemicals.
Keywords: land classification; capacity of land use and agrological classes